The Effectiveness of a Technological Pedagogical Content Knowledge Based Somatic, Auditory, Visual, Intellectual Learning Model in Developing Self Regulated Learning Among Pre-Service Elementary Teachers - Fina Fakhriyah; Siti Masfuah; Mark Jhon R. Prestoza; Putri Alifia Nur Meidina (Jurnal Pendidikan Sains Indonesia, 2025)
Self-regulated learning is a crucial competency that pre-service elementary teachers must possess, particularly in the face of the challenges of education in the digital era. This study aims to: (1) analyse the level and development of students' self-regulated learning (SRL), and (2) test the effectiveness of somatic, auditory, visual, and intellectual learning models based on technological pedagogical content knowledge in improving SRL. This study used a quasi-experimental design with an unequal control group. The sample consisted of 143 students in the Biophysics course. Data were collected through pre- and post-tests and an SRL questionnaire, and then analysed using paired sample t-tests and n-gain tests. The results showed a significant increase in SRL scores in the experimental group (gain = 12.7; p = 0.002), while the control group showed no significant changes. Although there was no significant difference in the final learning outcome scores, the technological pedagogical content knowledge (TPACK)-based somatic, auditory, visual, intellectual (SAVI) learning model was proven to be effective in improving SRL components, particularly in the application of learning strategies and planning. This study recommends the use of the SAVI learning model based on TPACK in pre-service teacher education